Analisis Perbedaan Nelayan Perikanan Laut dan Perairan Umum Daratan yang Memengaruhi PDRB di Jawa Timur - Ahdinia Intan Lestari; R.A. Norromadani Yuniati; Farizi Rachman (Proceeding Maritime Business Management Conference, 2024)
East Java Province has abundant potential in the fisheries sector, both production factors and geographical conditions of the sea. The production factor of capture fisheries in East Java in 2017-2022 tends to increase but contributes little to the GRDP of East Java. The variables used in this study are the number of fishermen and GRDP of districts/cities in East Java. The study aims to analyze the effect of the number of fishermen on GRDP in East Java and analyze the differences in each subsector. The research used a saturated sample technique, with panel data regression as the analysis test. The study is divided into two models, namely model I (marine fisheries) and model II (inland public waters). The results showed that in both models the number of fishermen had a significant positive effect on GRDP. This is because the increasing number of fishermen will increase the catch of fish and the income earned. The increased income will contribute to the economic growth of a region or what is referred to as GRDP. Marine fishermen tend to have more numbers than inland public water fishermen because a larger area will require more labor.